Getting hands dirty: on Adam Schaff’s political writings - Świrek, Krzysztof (Hybris, 2017)
Adam Schaff was one of the most important Marxist philosophers in Poland. His work well documents the time, when Marxism was an ’official philosophy’, burdened with political responsibilities and problems of strategy. The text is a critical analysis of Schaff’s political writings. It highlights the most specific traits of his often paradoxical position, that was termed in literature as ’orthodox-revisionism’. Schaff tried to meet double and often conflicting requirements: tried to develop Marxist theory by posing problems unforeseen by the classics, and to stay faithful to what he understood as strategic interests of socialist countries at the same time. It will be argued, that even in its theoretical shortcomings, his writings are still among the most important resources for reflection on complex and tragic history of the Left in 20th Century.